Innovative Teaching Technologies in Training Future Teachers to Form Coherent Speech of Junior Pupils - Maftyn, Larysa (Pedagogical Discourse, 2025)
Modern education is in a state of dynamic change, which requires new approaches to teacher training. Therefore, the relevance of the study is due to the new educational benchmarks and requirements of the State Standard of Primary Education, the need for professionally mobile, innovative teachers, the need to update the content and methods of professional training of students, and the demand for effective tools for developing the speech competence of younger students. The purpose of the article is to reveal the peculiarities of using innovative teaching technologies in the process of professional training of future primary school teachers to form coherent speech of junior schoolchildren; to substantiate effective forms, methods and means of teaching that contribute to the development of relevant professional competencies. To achieve the goal and solve the research tasks, a set of interrelated theoretical and empirical methods was used: analysis, generalization, and mathematization of scientific sources; comparative analysis of pedagogical technologies; observation of the educational process, study and analysis of educational programs and teaching materials. The article discusses the importance of using innovative technologies and interactive teaching methods in the process of professional training of future primary school teachers, in particular, the formation of coherent speech of younger students. The author emphasizes how these pedagogical tools help to form professional competencies and subject knowledge. The article presents the experience of methodological training of future primary school teachers at the Department of Pedagogy and Methods of Primary Education of Yuriy Fedkovych Chernivtsi National University in the process of studying the discipline «Development of Coherent Speech of Younger Students». The conclusions emphasize that the use of innovative teaching technologies ensures the quality of education and allows higher education students to develop appropriate skills, abilities, and competencies. It is important to choose the right technologies for a particular topic, as well as to provide appropriate training for students to use these tools properly.